1999
DOI: 10.1017/s0031182099004461
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of a Trichinella britovi gene encoding a cytoplasmic heat shock protein of 72 kDa

Abstract: A gene encoding a protein of 646 amino acid residues with a molecular mass of 71.3 kDa showing homology to the cytoplasmic form of the 70 kDa heat shock protein was cloned and sequenced from the nematode parasite Trichinella britovi (Tb). The gene was expressed in vitro as a protein of 71 kDa that was immunoprecipitated by a Trichinella-infected rabbit serum. Monospecific polyclonal antibodies raised against the recombinant Tb Hsp70 expressed in Escherichia coli, recognized a protein of 70 kDa by Western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…BLAST analysis revealed that AdTs1 had no homology with Trichinella antigens published in the GenBank. The guanine-cytosine (GC) content of this new T. spiralis gene (42 %) is very similar to those previously described (Sugane & Matsuura, 1990;Su et al, 1991;Vayssier et al, 1999), but is higher than the average GC percentage of the overall genome of parasitic nematodes (35 %) (Hammon & Bianco, 1992). Interestingly, some similarities were found between the AdTs1 protein and nuclear hormone receptors of mammals (rodents and human) or other species (ecdysteroid receptor from Tenebrio molitor or nuclear hormone receptor of Drosophila melanogaster).…”
Section: Discussionsupporting
confidence: 83%
“…BLAST analysis revealed that AdTs1 had no homology with Trichinella antigens published in the GenBank. The guanine-cytosine (GC) content of this new T. spiralis gene (42 %) is very similar to those previously described (Sugane & Matsuura, 1990;Su et al, 1991;Vayssier et al, 1999), but is higher than the average GC percentage of the overall genome of parasitic nematodes (35 %) (Hammon & Bianco, 1992). Interestingly, some similarities were found between the AdTs1 protein and nuclear hormone receptors of mammals (rodents and human) or other species (ecdysteroid receptor from Tenebrio molitor or nuclear hormone receptor of Drosophila melanogaster).…”
Section: Discussionsupporting
confidence: 83%
“…The 70-kDa Hsp of T. spiralis was detected by Western blotting using mAbs (Martinez et al 2000). The 70-kDa Hsp of T. britovi was detected in the nuclei of the muscle larvae but not in adult worm nuclei (Vayssier et al 1999). Martinez et al (1999) compared three stimuli, elevated temperature, hydrogen peroxide, and mebendazole for their ability to induce heat shock responses in T. spiralis muscle larvae and observed that the exposure to hydrogen peroxide resulted in the induction of constitutive and higher Hsps.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
“…Although Vayssier et al (1999) cloned and characterized the cytoplasmic hsps 70 and 72 of T. britovi, the structure of the hsp genes of other trichinellids remains unknown. Therefore, the present study was undertaken to clone and characterize the hsp 60 gene of T. spiralis.…”
Section: Introductionmentioning
confidence: 99%